Effect of La3+ cation solubility on the structural, magnetic and electrical properties of barium hexaferrite. Issue 6 (15th March 2021) - Mariño-Castellanos, P.; Guerrero, F.; Romaguera-Barcelay, Y.; Goveia-Alcaide, E.; Cotta, E.A.; Leyet, Y.; Anglada-Riveira, J.; Padrón-Hernández, E.; Peña-Garcia, R.
Abstract: In the present work, was studied the effect of the La 3+ cation solubility on the structural, magnetic and electrical properties of M-type barium hexaferrite (BaM). The Rietveld refinement revealed changes in the lattice parameters with increasing the La 3+ concentration. Variations in the bond length and the distortion index of 2b, 4f2 and 12k oxygen polyhedral were observed with the La 3+ insertion in the BaM structure. In addition to the BaM phase, secondary phases Fe2 O3 and LaFeO3 arise, whose concentrations depend on the La 3+ solubility. The magnetic properties are strongly affected by the La 3+ incorporation in the structure, as well as by the secondary phases. Changes in the oxidation state of Fe 3+ to Fe 2+ decreases the exchange interaction, resulting in the magnetic moments disturbance. The electrical properties are dependent on the La 3+ content and the secondary phase concentration. Undoped sample present the highest impedance values, decreasing linearly in all frequency range. For doped samples, the resistivity decreases in several orders due to the La 3+ incorporation, while the ac-conductivity remains constant at low frequencies and presents dispersion at high frequencies. The dielectric permittivity present space charge polarization mechanism generated by electron hopping from Fe 3+ to Fe 2+ ions. The Non-Debye-type relaxation and the conductivity transition of long and short range are suggested from the results of imaginary impedance and electric module. The bond valence model revealed that the most affected crystallographic sites are 2b, 4f2 and 12k, where the exchange of valence of Fe 3+ by Fe 2+ ions should take place.